2009
DOI: 10.1038/ejcn.2009.45
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre intake is inversely associated with carotid intima-media thickness: a cross-sectional assessment in the PREDIMED study

Abstract: Objective: To assess the association between the intake of dietary fibre and carotid intima-media thickness (IMT) in a Mediterranean population at high cardiovascular risk. Methods: Baseline cross-sectional assessment of 457 men and women (average age 67 years) from two different Spanish centres of the PREDIMED trial. A previously validated food frequency questionnaire (137 food items) was administered by trained dieticians in a face-to-face interview. Mean common carotid IMT was measured using B-mode ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 37 publications
2
18
1
Order By: Relevance
“…The results of our study can be supported by a randomized controlled trial reporting a slight regression in CCA‐IMT with dietary changes, which included an increased intake of fruit and vegetables over a 12‐month period 46. However, in observational studies, no associations have been observed between intakes of vegetables alone and carotid IMT, and they suggest fruit intake may be more beneficial 47, 48. Fruit intake, however, did not influence the association between total vegetable intake and CCA‐IMT in our study, and it was not itself an independent predictor.…”
Section: Discussionsupporting
confidence: 69%
“…The results of our study can be supported by a randomized controlled trial reporting a slight regression in CCA‐IMT with dietary changes, which included an increased intake of fruit and vegetables over a 12‐month period 46. However, in observational studies, no associations have been observed between intakes of vegetables alone and carotid IMT, and they suggest fruit intake may be more beneficial 47, 48. Fruit intake, however, did not influence the association between total vegetable intake and CCA‐IMT in our study, and it was not itself an independent predictor.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, at 3 mo, fiber intake was increased by 5 g/d (95% CI: 1, 8 g/d; P = 0.006) in the intervention group compared with the control group. Buil-Cosiales et al (29) showed that a 10-g increase in fiber from ,25 g/d to .35 g/d was associated with CCA IMT 0.051 mm lower, and only fiber consumption from fruit was inversely associated with CCA IMT. In addition, potassium intake was increased by 492 mg/d (95% CI: 94, 889 mg/d; P = 0.02) in the intervention group compared with the control group at 12 mo.…”
Section: Discussionmentioning
confidence: 97%
“…The intake of fibers contained in cereals, fruits, and vegetables [24], as part of a correct dietary regimen, further ameliorates lipid profile [25]. In particular, fruit consumption appears to be inversely correlated to the carotid intima-media thickness (an established surrogate marker of CVD) in adults [26]. In children, fiber intake should conventionally correspond (in weight) to years of age plus 5 g/d [2].…”
Section: Discussionmentioning
confidence: 98%